2017
DOI: 10.3389/fpls.2017.01977
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Chloris Species from Cuban Citrus Orchards and Determining Their Glyphosate-Resistance Status

Abstract: The Chloris genus is a C4 photosynthetic species mainly distributed in tropical and subtropical regions. Populations of three Chloris species occurring in citrus orchards from central Cuba, under long history glyphosate-based weed management, were studied for glyphosate-resistant status by characterizing their herbicide resistance/tolerance mechanisms. Morphological and molecular analyses allowed these species to be identified as C. ciliata Sw., Chloris elata Desv., and Chloris barbata Sw. Based on the glyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…In addition, the S C. barbata population showed LD 50 value (545 g ae ha −1 ) close to the standard dose, evidencing a certain innate tolerance level in this species. Sensitive populations of C. elata , C. ciliata , C. truncata and C. virgata also recorded high degrees of tolerance to glyphosate with LD 50 ranging from 515 to 1385 g ae ha −1 of glyphosate . Taking into account that controlling a weed population requires at least twice its estimated LD 50 , the standard dose of 720 g ae ha −1 used is not enough to control the S C. barbata population (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the S C. barbata population showed LD 50 value (545 g ae ha −1 ) close to the standard dose, evidencing a certain innate tolerance level in this species. Sensitive populations of C. elata , C. ciliata , C. truncata and C. virgata also recorded high degrees of tolerance to glyphosate with LD 50 ranging from 515 to 1385 g ae ha −1 of glyphosate . Taking into account that controlling a weed population requires at least twice its estimated LD 50 , the standard dose of 720 g ae ha −1 used is not enough to control the S C. barbata population (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contribution of glyphosate metabolism as a resistance mechanism is not clear, and so far occurs at significantly lower rates in glyphosate than glyphosate‐resistant transgenic crops carrying the glyphosate oxidoreductase (GOX) gene . In this respect, these studies demonstrated that treated weed plants, be they susceptible, tolerant or resistant, can metabolize minimal amounts of glyphosate into non‐toxic substances, which could be a biological characteristic . However, metabolism does not appear to be related to resistance to glyphosate of the R1 and R2 C. barbata populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations